Pengaruh Gaya Kepemimpinan, Tingkat Pendidikan, Dan Lingkungan Kerja Terhadap Kinerja Karyawan (Studi pada PT. Galaxy Surya Panelindo Lumajang) - Aditya Yoga Pratama; Abdul Kodir Djaelani; Fahrurrozi Rahman (UNIVERSITAS ISLAM MALANG, 2022)
Abstract The purpose of the study was to describe leadership style, level of education and work environment and to determine its effect on employee performance simultaneously and partially. This research method uses quantitative methods with this type of research (explanatory research). The sample of this research is the employees of PT. GALAXY SURYA PANELINDO using the slovin formula produced as many as 67 respondents. Methods of data collection using a questionnaire. The analytical method used in this study is multiple regression analysis with the help of SPSS 16. for windows. The results of this study indicate that: (1) simultaneously there is a significant influence between leadership style, education level and work environment on employee performance at PT. GALAXY SURYA PANELINDO. while partially (2) leadership style has a significant effect on employee performance (3) education level has a significant effect on employee performance (4) work environment partially affects employee performance at PT. GALAXY SURYA PANELINDO. Keywords : Leadership style, education level, work environment and employee performance.